Spray layer-by-layer films based on phospholipid vesicles aiming sensing application via e-tongue system - Aoki, P. H. B. [UNESP]; Volpati, D. [UNESP]; Cabrera, F. C. [UNESP]; Trombini, V. L. [UNESP]; Riul, A.; Constantino, C. J. L. [UNESP] (Elsevier B.V., 2012)
The Layer-by-Layer (LbL) technique via spraying (spray-LbL) has been applied as new and alternative methodology to fabricate ultrathin films due to its versatility in relation to the conventional dipping-LbL method, mainly in terms of faster layer deposition and larger coated area. In this work, the possibility of immobilizing vesicles of dipalmitoyl phosphatidyl glycerol (DPPG) phospholipid onto alternating layers of the polyelectrolyte poly(allylamine hydrochloride) (PAH) using the spray-LbL method was investigated, being the results compared to the conventional dipping-LbL method. The growth of (PAH/DPPG)(n) spray-LbL films was systematically monitored by quartz crystal microbalance (QCM) and ultraviolet-visible (UV-vis) absorption spectroscopy, revealing a linear increase of the absorbance vs deposited layers. In relation to a possible electrostatic interaction between the groups PO4- (DPPG) and NH3+ (PAH), it was observed through Fourier transform infrared (FTIR) absorption spectroscopy that the spectrum recorded for the spray-LbL film is basically a simple superposition of the FTIR spectra from PAH and DPPG casting films. The latter indicates a weak interaction between both materials, differently of the trend observed for (PAH/DPPG)(n) grown via dipping-LbL method. Atomic force microscopy (AFM) images of spray-LbL films showed evidences that the DPPG vesicles present in the aqueous dispersion are not destroyed when submitted to pressure conditions during the spray deposition. However, comparing to dipping-LbL, the DPPG vesicles do not cover completely the PAH layer for the spray-LbL film, which was further confirmed by surface-enhanced Raman scattering (SERS) measurements. Moreover, the AFM analysis showed that the spray-LbL deposition led to thicker PAH/DPPG bilayers in average than via dipping-LbL for the same concentrations of PAH solution and DPPG dispersion. which is consistent with QCM and UV-vis absorption results. PAH/DPPG films deposited by dipping- and spray-LbL techniques and also by Langmuir-Blodgett (LB) onto Pt interdigitated electrodes composing an array of sensing units (e-tongue) were applied in the detection of a xanthene derivate (eosin) in diluted solutions (10(-9), 10(-7) and 10(-6) M). Despite the LB and LbL films are formed by the same materials (PAH and DPPG), it was found that their different molecular architectures play an important role on the electrical response of Pt interdigitated electrodes in impedance spectroscopy measurements. The high sensitivity reached by these sensing units was intimately related to changes in the film morphology caused by the adsorption of the eosin molecules onto the film surfaces during electrical measurements, as evidenced by micro-Raman technique. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Spray layer-by-layer film; Phospholipids; Impedance spectroscopy; Xanthene